GAMBARAN MOTIVASI BELAJAR SIMULASI DIGITAL MENGGUNAKAN SMARTPHONE - Yul, Fadlul Amdhi; Ramadani, Niska (Jurnal EDik Informatika, 2020)
This study focuses on the description of learning motivation through smartphones on digital simulation subjects. The purpose of this studyis to find out how the picture of student motivation through smartphones on digital simulation subjects in class X TKJ 9 Muhammadiyah Bengkulu City. The method used in this research isdescriptive qualitative. The subjects of this study were 15 students of class X TKJ. Data collection techniques are using observation, interviews, documentation. The results of this study indicate that theuse of a smartphone in school can be used as a support in learning motivation, because a smartphone is needed as a tool used by students to search for material, assignments given by teachers whenthere are no learning books. However, the use of this smartphone needs supervision from both parents and teachers at school, so that it can help in increasing student motivation.